Resolving the internal morphology of core–shell microgels with super-resolution fluorescence microscopy. Issue 1 (4th December 2019) - Otto, Pia; Bergmann, Stephan; Sandmeyer, Alice; Dirksen, Maxim; Wrede, Oliver; Hellweg, Thomas; Huser, Thomas
Abstract : We investigate the internal structure of smart core–shell microgels by super-resolution fluorescence microscopy by combining of 3D single molecule localization and structured illumination microscopy using freely diffusing fluorescent dyes. Abstract : We investigate the internal morphology of smart core–shell microgels by super-resolution fluorescence microscopy exploiting a combination of 3D single molecule localization and structured illumination microscopy utilizing freely diffusing fluorescent dyes. This approach does not require any direct chemical labeling and does not perturb the network structure of these colloidal gels. Hence, it allows us to study the morphology of the particles with very high precision. We found that the structure of the core-forming seed particles is drastically changed by the second synthesis step necessary for making the shell, resulting in a core region with highly increased dye localization density. The present work shows that super-resolution microscopy has great potential with respect to the study of soft colloidal systems.